1463. Activity of Delafloxacin against Multi-Drug-Resistant Fastidious Respiratory Pathogens from European Medical Centers (2014-2019) - Shorttidge, Dee (Open Forum Infect Dis, 2020)
BACKGROUND: Delafloxacin (DLX) is an anionic fluoroquinolone (FQ) that has been approved in the United States and in Europe for the treatment of acute bacterial skin and skin structure infections and was recently approved in the US for treatment of community-acquired bacterial pneumonia (CABP). In the present study, in vitro susceptibility (S) results for DLX and comparator agents were determined for CABP pathogens including Streptococcus pneumoniae (SPN), Haemophilus influenzae (HI), H. parainfluenzae (HP) and Moraxella catarrhalis (MC) clinical isolates from European hospitals participating in the SENTRY Program during 2014-2019. METHODS: A total of 2,835 SPN, 1,484 HI, 959 MC, and 20 HP isolates were collected from community-acquired respiratory tract infections (CARTI) during 2014-2019 from European hospitals. Sites included only 1 isolate/patient/infection episode. Isolate identifications were confirmed at JMI Laboratories. Susceptibility testing was performed according to CLSI broth microdilution methodology, and EUCAST (2020) breakpoints were applied where applicable. Other antimicrobials tested included levofloxacin (LEV) and moxifloxacin (MOX; not tested in 2015). Multidrug-resistant (MDR) SPN isolates were categorized as being nonsusceptible (NS) to amoxicillin-clavulanate, erythromycin (ERY), and tetracycline; other SPN phenotypes were ERY-NS, or penicillin (PEN)-NS. β-lactamase (BL) presence was determined for HI, HP, and MC. RESULTS: The activities of the 3 FQs are shown in the table. The most active agent against SPN was DLX, with the lowest MIC(50/90) values of 0.015/0.03 mg/L. DLX activities were the same when tested against the MDR or PEN-NS for SPN phenotypes. ERY-NS isolates had DLX MIC(50/90) results of 0.015/0.03 mg/L. DLX was the most active FQ against HI, HP, and MC. BL presence did not affect FQ MIC values for HI or MC; only 1 HP isolate was BL-positive. CONCLUSION: DLX demonstrated potent in vitro antibacterial activity against SPN, HI, HP, and MC. DLX was active against MDR SPN that were NS to the agents commonly used as treatments for CABP. These data support the utility of DLX in CABP including when caused by antibiotic resistant strains. Table 1 [Image: see text] DISCLOSURES: Jennifer M. Streit, BS, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Merck (Research Grant or Support)Paratek Pharma, LLC (Research Grant or Support) Robert K. Flamm, PhD, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Amplyx Pharmaceuticals (Research Grant or Support)Basilea Pharmaceutica International, Ltd (Research Grant or Support)Department of Health and Human Services (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)